A genomic analysis of twinning rate and its relationship with other reproductive traits in Holstein-Friesian cattle - Brian W. Kirkpatrick; Donagh P. Berry (Journal of Dairy Science)
ABSTRACT: Twin births in dairy cattle is generally unfavorably associated with reproductive performance and calf survival in dairy cows. Genetic selection to reduce twinning rate in dairy cattle may be desirable, provided no undesirable correlated responses in other traits exist. The current study was undertaken to characterize the genomic architecture of twinning rate in the Irish Holstein-Friesian population, and to quantify the genetic relationship of twinning with other reproductive traits and milk yield. Calving records from the years 1996 to 2022 were used together with pedigree information to generate breeding value estimates for twinning rate. Genome-wide association analyses of twinning rate, calving interval, cow survival and age at first calving were conducted using de-regressed breeding values estimates for 2,656 Holstein-Friesian sires. Full genome sequence data imputed from ∼50,000 single nucleotide polymorphisms were available for all sires. The h2 of twinning rate was 0.0118 ± 0.0010. Twinning rate was very weakly genetically correlated with both milk yield (0.13) and the reproductive traits (−0.26 to 0.14). Genomic analyses detected an association with twinning rate at 31.1 Mb on BTA11 in close proximity to genes for FSH receptor and luteinizing hormone-chorionic gonadotropin receptor, supporting previous studies. The most significant SNP in this region was not associated with milk yield, indicating the potential for selection to reduce twinning rate without detrimentally affecting milk yield. Novel SNP associations with age at first calving on BTA27 and from a meta-analysis of calving interval and age at first calving on BTA29 were also identified and are candidates for future validation and study.